A personalized intervention to prevent depression in primary care: cost-effectiveness study nested into a clustered randomized trial. - Fernández, Anna; Mendive, Juan Manuel; Conejo-Cerón, Sonia; Moreno-Peral, Patricia; King, Michael; Nazareth, Irwin; Martín-Pérez, Carlos; Fernández-Alonso, Carmen; Rodríguez-Bayón, Antonina; Aiarzagüena, José María; Montón-Franco, Carmen; Serrano-Blanco, Antoni; et al. (BioMed Central, 2018)
Depression is viewed as a major and increasing public health issue, as it causes high distress in the people experiencing it and considerable financial costs to society. Efforts are being made to reduce this burden by preventing depression. A critical component of this strategy is the ability to assess the individual level and profile of risk for the development of major depression. This paper presents the cost-effectiveness of a personalized intervention based on the risk of developing depression carried out in primary care, compared with usual care.
Keywords: Atención primaria - Aspectos económicos; Depresión mental - Prevención; Análisis cluster; Análisis coste-beneficio; Evaluación del riesgo; Cluster Analysis; Cost-benefit analysis; Depression / economics; Depression / prevention & control*; Humans; Primary health care / economics*; Primary health care / methods*; Quality-adjusted life years; Risk assessment